2009
DOI: 10.3744/snak.2009.46.3.325
|View full text |Cite
|
Sign up to set email alerts
|

Process Improvements for Elevating Pre-outfitting Rate of FPSO

Abstract: Generally, functional design of FPSO has been done by the engineering firm designated by ship owner. Main equipment such as topside facility is imported from abroad. But sometimes, OFE (Owner Furnished Equipment) does not satisfy the PND (Product Need Date) of each production stage because the delivery date of OFE is not scheduled to satisfy the PND. And sometimes many loose items and equipment are complex from engineering which does not consider pre-outfitting. Main objective of this study is process improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This ultimately results in precise scheduling of product delivery and is accompanied by the reduction of production time, cost, and risk. Shin et al [4] reported that the improvements in the construction method resulted in a higher preoutfitting rate followed by a more efficient scheduling and faster production. In their study, the reduction in the FPSO production time only reached 44%.…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This ultimately results in precise scheduling of product delivery and is accompanied by the reduction of production time, cost, and risk. Shin et al [4] reported that the improvements in the construction method resulted in a higher preoutfitting rate followed by a more efficient scheduling and faster production. In their study, the reduction in the FPSO production time only reached 44%.…”
Section: Case Studymentioning
confidence: 99%
“…The constructed module needs to be connected to the other blocks. Generally, the specific locations for connection work, such as junctions of pipes, are marked on the panel sides of the adjacent blocks [4]. However, such markings cannot be labeled on an open block, which does not have a connection panel.…”
Section: Introductionmentioning
confidence: 99%
“…The periods of installation are spread over the construction schedule. For reference, the outfitting installation is possible to be divisible in the precedent (Shin et al, 2009), the dock, and the quay installation with the time when outfitting equipment is established. In case of the precedent installation, it can be subdivided by "Hull structure outfitting," "Unit outfitting," "On-block outfitting," and "Pre-Erection outfitting".…”
Section: Definition and Necessity Of Hole-plan Systemmentioning
confidence: 99%